Kewenangan Dewan Perwakilan Daerah Setelah Adanya Keputusan Mahkamah Konstitusi Nomor 92/PUU-X/2012 - Zahratul Idami (Universitas Syiah Kuala, 2014)
Regional House of Representative is the state institution existing after the fourth amendment of the Constitution 1945. Its functions have been worded in Article 22 of the Constitution. The element of the institution is people representatives from region is working for their regions.before the Court decision, it is deemed as a body has no significant rules as a legislation body. The members are chosen by voters directly making it should have more power. It is relevant due to the fact that the problems are bigger. If it is deemed that the members are directly elected, the consideration is too weak as it is rule by the election in 2004 has ruled this. The court decision on 27 March 2013 making the power has been in accordance with the constitution. Given to this, the body can have more roles in handling the interests of the people. Thus, it is important to explore the legislation after the decision. The Authority of Regional House of Representative in Indonesia after the Decision of the Constitutional Court Number 92/PUU-X/2012